FENOMENA BERMAIN GAME ONLINE MOBILE LEGEND TERHADAP PERILAKU KOMUNIKASI ANTAR PRIBADI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS DARMA AGUNG MEDAN - Daniel P Bangun; Elza Ismy Sara Sintia Harahap (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
The development of Internet cannot be separated from the what is called new media. New media offers users to choose the appropriate information to use, control information, interactivity is the main concept of understanding new media, the emergence of virtual reality, virtual communities and virtual identities appear with the presence of new media. Currently there are games that are very addictive in society. namely Mobile Legends Game. Mobile legend players tend to be less concerned about their surroundings, sleep long, get information late and are lazy. This study uses a qualitative research method where the research method is based on the philosophy of postpositivism, which is used to examine the condition of natural objects, with the object of research being a phenomenon from playing mobile legend and how is the interpersonal communication of mobile legend players. The conclusion from the phenomenon of playing the Oline Mobile Legend game on interpersonal communication behavior of students of the Faculty of Economics, Darma Agung University. On the positive side, they get great satisfaction. While on the negative impact, they tend to lose track of time, forget assignments, forget to sleep more often and even tend not to feel sorry for sacrificing the materials they spend in order to meet their needs such as buying more packages to play games and to buy premium items in the mobile legend game. In addition, it has a negative impact in terms of communication or interpersonal communication relationships that eliminate empathy, because they like to give insults and blasphemy to fellow players and can be to non-players and with friends who do not play mobile legend even though they create intimacy with fellow mobile legend players and have a language which is understood only by the game player.